TOURISM PROMOTION STRATEGY OF LINGGA MELAYU REGENCY TOWARDS HISTORICAL AND CULTURAL TOURISM TO JOHOR BARU - Soekamto, Linarko; Amran, Amran (Universitas PGRI Sumatera Barat, 2025)
The Riau Lingga Kingdom is an Islamic kingdom located in the Riau Lingga Islands, Lingga district, Riau. The Riau Lingga Kingdom was founded around 1828 AD to 1911 AD. This kingdom reached the peak of its glory during the reign of Sultan Sulaiman Badrul Alamsyah II Yang Dipertuan Besar Riau Lingga IV, reigning from 1857 to 1883 AD.The Riau Lingga Kingdom had an important role in the development of the Malay language to its current form as Indonesian. During the time of the Riau Lingga kingdom, Malay became a standard language on a par with other major languages in the world, which were rich in literature and had monolingual dictionaries. For this reason, Lingga district is often called the country of the Mother of Malay Land.Apart from being famous as a historical tourist destination, Lingga district often attracts the attention of many local and foreign tourists. Apart from historical tourism, Lingga district also has natural and cultural tourism.With so many tourist destinations in Lingga district, the local government in collaboration with the tourism department always carries out promotions at both local and international events. This is especially true for Malaysia. Due to the historical ties that exist between Malaysia and Indonesia.Keywords: Daik Lingga kingdom, tourism in Lingga district